Radial growth projections reveal site-specific futures of different oak species with contrasting water availability in SW Hungary - Móricz, Norbert; Mészáros, Ilona; Illés, Gábor Zoltán; Garamszegi, Balázs; Eötvös, Csaba Béla; Kern, Anikó; Hirka, Anikó; Berki, Imre; Borovics, Attila; Hollós, Roland; Németh, Tamás Márton (Frontiers in Forests and Global Change, 2025)
The growth and vitality of forest ecosystems in Central Europe are expected to be affected by climate change, posing a challenge for forest management. In this study, we examined and projected the relationship between growth and climate for dominant sessile oak (Quercus petraea (Matt.) Liebl.) and Turkey oak (Quercus cerris L.) trees in two sites in Hungary, each with different water availability. We developed a single linear mixed model based on tree age, climatic water balance and insect outbreak for the study period (1971–2021) to estimate the impact of projected climate change in the 21st century on basal area increments until 2100 using two climate scenarios (RCP4.5 and RCP8.5). Our study suggests that the growth response of oak species to different seasonal water balances is site and species-specific. We found that the water balance of the previous winter had a significantly greater influence on the growth in the stands of the dry site than in the stands of the wet site. Q. cerris reacted more sensitively to the water balance conditions of the previous summer than Q. petraea. Predictive models forecast a general growth decline of up to 10.8% for both oak species during the 21st century compared to past growth with a significant change according to the RCP8.5 scenario. Additionally, the models predict a significantly greater decrease in growth in the more humid site compared to the xeric site which could be attributed to the site-specific response of growth to the winter water balance. At the same time, we did not detect significant differences in the future growth of the two oak species. These findings provide insights into the climate-related factors influencing growth in Hungarian oak forests.